What Happens if Central Banks Misdiagnose a Slowdown in Potential Output - Bakker, Bas (IMF Working Papers; Working Paper ;, 2019)
In the last few decades, real GDP growth and investment in advanced countries have declined in tandem. This slowdown was not the result of weak demand (there has been no shift along the Okun curve), but of a decline in potential output growth (which has shifted the Okun curve to the left). We analyze what happens if central banks mistakenly diagnose the problem as insufficient demand, when it is actually a supply problem. We do this in a real model, in which inflation is not an issue. We show that aggressive central bank action may revive gross investment, but it will not revive net investment or growth. Moreover, low interest rates will lead to an increase in the capital output ratio, a low return on capital and high leverage. We show that these forecasts are in line with what has happened in major advanced countries.